Unique Patterns of H3K4me3 and H3K27me3 in 2-Cell-like Embryonic Stem Cells - Zhang, Yanping (Stem Cell Reports, 2021)
A small subgroup of embryonic stem cells (ESCs) exhibit molecular features similar to those of two-cell embryos (2C). However, it remains elusive whether 2C-like cells and 2C embryos share similar epigenetic features. Here, we map the genome-wide profiles of histone H3K4me3 and H3K27me3 in 2C-like cells. We found that the majority of genes in 2C-like cells inherit their histone status from ESCs. Among the genes showing a switch in their histone methylation status during 2C-like transitions, only a small number acquire 2C-embryo epigenetic signatures. In contrast, broad H3K4me3 domains display extensive loss in 2C-like cells. Most of the differentially expressed genes display decreased H3K4me3 and H3K27me3 levels in 2C-like cells, whereas de novo H3K4me3 deposition is closely linked with the expression levels of upregulated 2C-specific genes. Taken together, our study reveals the unique epigenetic profiles of 2C-like cells, facilitating the further exploration of totipotency in the future.